How Do Service Quality and Exhibition Experience Impact Revisit Intention: Evidence from Metaverse Exhibitions - Jinquan Zhou; Ho Hong-Wai; Zhuoxiang Wang (Bright Publisher, 2026)
This study investigates the impact of metaverse exhibitions on consumer behavior, focusing particularly on revisit intention. Using a quantitative research design, data were collected from 324 participants who attended exhibitions in Macau and Hengqin. The results obtained through Partial Least Squares Structural Equation Modeling (PLS-SEM) reveal that metaverse exhibitions significantly enhance revisit intention (β = 0.171, p = 0.007), perceived service quality (β = 0.237, p < 0.001), and exhibition experience (β = 0.284, p < 0.001). Both perceived service quality (β = 0.210, p < 0.001) and exhibition experience (β = 0.243, p < 0.001) positively influence revisit intention and act as significant mediators in these relationships. The total effect of the metaverse exhibition on revisit intention was β = 0.304 (p < 0.001), confirming strong direct and indirect effects. These findings underscore the critical role of service quality and experiential engagement in shaping visitor loyalty within virtual environments. Practically, the study suggests that exhibition organizers should leverage VR/AR technologies and interactive design strategies to enhance immersion and foster repeat visitation. Overall, this research highlights the transformative potential of the metaverse in redefining audience interaction and loyalty in virtual exhibition platforms.